Relationship Between Protein Kinase C and Diabetic Nephropathy Patients in Al Anbar City - Duaa H. Rajab, Wisam M. Mohammad (Pakistan Journal of Medical & Health Sciences, 2022)
Background : Diabetic syndrome is characterized by increase blood sugar and resistance to insulin. It is linked to macrovascular and microvascular complications such as nephropathy, neuropathy, and retinopathy . the aim of this study to investigate the relationship protein kinase C and diabetic nephropathy. Material and Methods: The study was include 84 samples , 36 of them with type 2 diabetes, 23 of them with diabetic nephropathy, and 25 healthy controls population , all of whom were over the age of 40. ELISA was used to calculate the protein kinase C level, fasting serum sugar , Glycated Hemoglobin ,Urea, Creatinine, Total protein, Albumin, and globulin were all found. Body mass index was also calculated. Result : the study result shown approximately same level between healthy and patients groups and this also associated with increase in fasting serum sugar , Glycated Hemoglobin , Urea , Creatinine and body mass index in patients group compared to Healthy controls group. Conclusion: serum protein kinase C shown non-significant difference between healthy and control patients.